PENGARUH PEMASARAN TEDY LOTION TERHADAP APLIKASI BERBASIS AR (AUGMENTED REALITY) - Ari Kurniawan Daulay; Rizki Irianto; Rini Aprilia Siahaan; Elisa Margareth Sihombing; Muhammad Zainuddin Lubis (Politeknik Negeri Batam, 2019)
The number of natural-based cosmetic products on the market is increasing. One of the natural ingredients that can be used is golden sea cucumber. TEDY lotion is a skin care product with collagen extract and gamapeptide from golden sea cucumber as the ingredients. The purpose of this article is to analyze the use of TEDY AR application on product sales. The method used is by using a questionnaire that has been tested, which is validity test. The validity test is then concluded to be a diagram through statistical formulation. The result showed, 73% like the product, 22% really like and 5% unlike. Meanwhile, the results of the questionnaire the application show that 44% strongly agreed, 45% agreed and 11% chose neutral. Therefore, it can be concluded that use of applications in helping sales have a positive impact. We hope this product can create a business opportunity for the future.